GADGET, GAYA PENGASUHAN, DAN TANTRUM PADA ANAK - Widya Maselina Tulya; Ayu Septiyani Sejahtera; Theodora Eka Cahya Lestari; Maria Joanna Witami Putri (Faculty of Psychology, Diponegoro University, 2025)
Ariani, A. (2017). Effects of playing with gadgets on elementary school children in urban and rural environment. In Health Science International Conference (HSIC 2017) (pp. 22-27). Atlantis Press. https://www.atlantis-press.com/article/25885821.pdfAzwi, A. I., Yenni, Y., & Vianis, O. (2022). Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Sosial Emosional Anak Yang Menggunakan gawai Pada Anak Usia Dini. REAL in Nursing Journal, 5(1), 24–24. https://doi.org/10.32883/rnj.v5i1.1507Fitzpatrick, C., Harvey, E., Cristini, E., Laurent, A., Lemelin, J., & Garon-Carrier, G. (2022). Is the Association Between Early Childhood Screen Media Use and Effortful Control Bidirectional? A Prospective Study During the COVID-19 Pandemic. Frontiers in Psychology, 13. https://doi.org/10.3389/fpsyg.2022.918834 Herdiana, M. F. P., & Santoso, M. B. (2024). FENOMENA KECANDUAN gawai PADA ANAK USIA PRA SEKOLAH AKIBAT PERGESERAN NILAI BUDAYA DAN FAKTOR KOGNITIF SOSIAL. Jurnal Penelitian dan Pengabdian Kepada Masyarakat (JPPM), 5(3), 150-165. https://doi.org/10.24198/jppm.v5i3.61521 Khoirul, A., Azizah, N. N., Salwa, N. S., & Fidrayani, N. F. (2024). Meta Analisis Pengaruh Pola Asuh Dalam Memberikan gawai Terhadap Sosial Emosional Anak Usia Dini. Khirani, 2(2), 117–124. https://doi.org/10.47861/khirani.v2i2.1081Lindriany, J., Hidayati, D., & Nasaruddin, D. M. (2023). Urgensi Literasi Digital Bagi Anak Usia Dini Dan Orang Tua. Journal of Education and Teaching (JET), 4(1), 35–49. https://doi.org/10.51454/jet.v4i1.201 Mulfiani, T. N., & Rakimahwati. (2022). Case study of tantrum behavior in early childhood, 15(3), 1-5. https://doi.org/10.35445/alishlah.v15i3.4173 Mylitenotes.com. (2024). Penyuluhan Dampak Kecanduan Gadget pada Anak - Website LLDIKTI Wilayah V. LLDikti Wilayah V Yogyakarta. https://lldikti5.kemdikbud.go.id/home/detailpost/penyuluhan-dampak-kecanduan-gadget-pada-anak#: :text=Berdasarkan%20data%20BPS%20%2C%20jumlah%20pengguna,memicu%20kecanduan%20gadget%20pada%20anak.Nurjanah, A., Suyadi, & Diana, R. R. (2024). Dampak penggunaan gawai terhadap kecerdasan emosi anak usia dini. Jurnal Pendidikan Anak Usia Dini, 5(1), 32–44. https://journal.ibrahimy.ac.id/index.php/Atthufulah/article/view/3615/2708 Novalia, R., & Kusayang, T. (2024). Analysis of Parenting Patterns for Early Childhood with gawai Addiction. JOYCED: Journal of Early Childhood Education, 4(2), 130-140. DOI: 10.14421/joyced.2024.42-05. https://doi.org/10.14421/joyced.2024.42-05 Nuria, R., & Anam, K. (2022). Dampak Gaya Pengasuhan Orang Tua terhadap Sikap Nomophobia pada Anak. Jurnal Ilmu Pendidikan Dan Sains Islam Interdisipliner, 63-69. https://doi.org/10.59944/jipsi.v1i2.39 Putri, N. R. I. A. T., Astuti, V. W., & Zuhrufillah, I. (2023). Penggunaan gadget dan kejadian temper tantrum pada anak usia 1 hingga 5 tahun. Jurnal Keperawatan Raflesia, 5(1), 47-56.https://doi.org/10.33088/jkr.v5i1.907Pramudyani, A. V. R. (2020). The Effect of Parenting Styles for Children’s Behaviour on Using Gadget at Revolution Industry. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(1), 51. http://dx.doi.org/10.31004/obsesi.v5i1.520 Radesky, J. S., Kaciroti, N., Weeks, H. M., Schaller, A., & Miller, A. L. (2022). Longitudinal associations between use of mobile devices for calming and emotional reactivity and executive functioning in children aged 3 to 5 years. JAMA Pediatrics, 177(1). https://doi.org/10.1001/jamapediatrics.2022.4793 Rahmawati, M., & Latifah, M. (2020). Penggunaan gawai, interaksi ibu-anak, dan perkembangan sosial-emosional anak prasekolah. Jurnal Ilmu Keluarga dan Konsumen, 13(1), 75–86. https://doi.org/10.24156/jikk.2020.13.1.75 Ramandhani, D. F., Arbarini, M., & Loretha, A. F. (2024). Milenial Parents’ Parenting Patterns are in Danger Use of Early Children’s Gadgets. Jurnal Pendidikan Anak Usia Dini Undiksha, 11(3), 373–382. https://doi.org/10.23887/paud.v11i3.67258Rizqi, N. P. A., Kuntoro, I. A., & Halim, L. (2022). Urban–Rural Influences on Parenting and Theory of Mind Development: An Intracultural Comparative Study in Indonesia. Psychological Research on Urban Society, 5(1), 30. https://doi.org/10.7454/proust.v5i1.126 Robson, D. A., Allen, M. S., & Howard, S. J. (2020). Self-regulation in childhood as a predictor of future outcomes: A meta-analytic review. Psychological bulletin, 146(4), 324. https://core.ac.uk/download/pdf/287817388.pdfSehularo, L. A., Molato, B. J., Mokgaola, I. O., & Gause, G. (2021). Coping strategies used by nurses during the COVID-19 pandemic: A narrative literature review. Health SA Gesondheid, 26. https://doi.org/10.4102/hsag.v26i0.1652Snyder, H. (2019). Literature review as a research methodology: An overview and guidelines. Journal of Business Research, 104(1), 333–339. ScienceDirect. https://doi.org/10.1016/j.jbusres.2019.07.039 Suhana, M. (2017). Influence of gadget usage on children's social-emotional development. In International conference of early childhood education (ICECE 2017) (pp. 224-227). Atlantis Press. https://www.atlantis-press.com/proceedings/icece-17/25889776 Waruwu, M. (2024). Pendekatan penelitian kualitatif: Konsep, prosedur, kelebihan dan peran di bidang pendidikan. Afeksi: Jurnal Penelitian Dan Evaluasi Pendidikan, 5(2), 198-211. https://pdfs.semanticscholar.org/8de8/be521b4102a42c318fec3d4ec4dcd375ff94.pdf Yan, Z., Lin, W., Ren, J., Ma, Q., & Qin, Y. (2024). Parenting styles and young children’s problem behaviours: The mediating role of electronic media usage. Early Child Development and Care, 194(13-14), 1435-1451. https://doi.org/10.1080/03004430.2024.2360513Zhao, J., Wu, M., Wu, L., Hou, H., Xie, J., Su, C., ... & Wu, J. (2024). Parental mindful parenting and adolescent resilience: the chain mediating role of self-compassion and emotion regulation. Current Psychology, 43(41), 32399-32411. https://doi.org/10.1007/s12144-024-06743-6